OPTIMASI ERMENTASI TEPUNG SINGKONG DAN APLIKASINYA PADA PEMBUATAN MAKANAN STIK - Suladra, Made (Universitas Widya Mataram, 2017)
The research was designed to determine the optimal fermentation time and the amount of cassava flour which can be used to produce sticks food crispy cassava flour. This research was done in two stages; The first stage, the optimization of fermentation used completely randomized design (CRD) with time at room temperature for fermentation; 1 day, 2 days 3 days and 4 days. The water content, total acid content and fiber content were analyzed. The second stage, cassava starch fermentation time selected was used for production of food sticks using a CRD with 4 treatments of cassava flour; 0%, 25%, 50%, 75%. baking testing, moisture, reducing sugar, crude fiber content, and organoleptic tests were analyzed. Data were analyzed by using ANOVA and the differences among treatments were tested by the method Duncan`s Multiple Ranges Test (DMRT) at the level of 5%. The results showed shredded cassava fermentation by R. oryzae AT3 at room temperature for 3 days in a sealed plastic to produce cassava flour that have; the water content of 13.10%, total acid 1.01%, crude fiber 3.08%, and white flour. Stick dough composition consisting of 50% flour and 50% of cassava starch fermented for 3 days were the best sticks food, preferred, and have organoleptic properties; crisp texture, light brown and slightly savory taste tasted cassava flour. Stick food with the addition of 50% cassava flour has a water content of 2.24%, crude fiber of 2.23%, reduced sugar of 2.27%, and fried after baking of 77.50%.